Evaluating SVD and DTCWT based Hybrid Video Watermarking using Chrominance Embedding - et al., Dr. Geetamma Tummalapalli (International Journal of Advanced Science and Technology, 2019)
As an unauthorized copy of a video can be modiﬁed, mass-produced, uploaded online and distributed globally, protecting its content from illegal distribution is becoming an important issue to be addressed. As the digital video watermarking is a possible way of protecting these views from unauthorized distribution, a digital video watermarking method is proposed. This paper implements the digital watermarking method for hybrid video. In this method, the watermark is embedded in the chrominance blue channel of a YUV representation using the dual-tree complex wavelet transform (DTCWT). SVD decomposes the watermark detailed coefficient matrix into 3 individual matrices where U, V are orthogonal and S is a singular matrix. The singular matrix S is used as watermark in the video stream, whereas the combination of orthogonal matrices U and V is used as watermark in audio stream. At the time of recovery of the watermark the S, U, and V matrices, which are extracted from watermarked video and audio, are combined to improve robustness of the algorithm. This combination procedure makes the algorithm as blind.